Autoria docente de jogos digitais e os movimentos de ruptura com a consciência ingênua: a experiência de futuros professores de Matemática sob a ótica sociotécnica - Nunes, Daniel Martins (Universidade Federal de São Carlos, 2026)
This doctoral research, set in the North of Minas Gerais and inspired by João Guimarães Rosa's concepts of “Sertão” (Backlands) and “Travessia” (Crossing), investigates the initial education of Mathematics teachers in the face of challenges in a context mediated by digital artifacts. The study problematizes the instrumental view and technological determinism, manifested under the logic of “technological salvationism.” In opposition to this dominant view, the defended thesis is that Teacher Authorship of digital games acts as a sociotechnical formative device, capable of stressing the naive consciousness about technology and breaking the illusory belief in its salvationist power. This authorship transcends the mere technical production of the artifact, configuring itself as a recursive and inseparable cycle of creating to apply, and applying to (re)signify the creation. Accordingly, the guiding research problem was defined as: What are the contributions and limits of a formative experience based on Teacher Authorship for the professional constitution of pre-service Mathematics teachers, grounded in their perceptions of the design, development, and mediation of digital games in teaching? The general objective was established to investigate the contributions and limits of a formative experience based on Teacher Authorship for the education of Mathematics teachers, analyzing the perceptions and reflections constructed by pre-service teachers based on the experience of conception, programming, and didactic use of digital games. The specific objectives unfold as follows: i) to understand the implications of Teacher Authorship in the constitution of the participants' perceptions regarding the tensions, algorithmic barriers, and reflections experienced during the digital game development process; and ii) to analyze the pre-service teachers' reflections and perceptions regarding the potentialities and limits of pedagogical mediation, evidenced through the experience of using these authorial artifacts in real teaching contexts in Basic Education. Grounded in Brigitte Albero's Sociotechnical Approach, Álvaro Vieira Pinto's philosophy of technology, and the assumptions of experience (Jorge Larrosa) and reflection (John Dewey), the research adopted a qualitative approach. Data were produced at the Federal Institute of Northern Minas Gerais (IFNMG – Januária Campus), where four pre-service teachers experienced “Teacher Authorship,” which consisted of designing, coding, and mediating the use of their own games in public schools. Data interpretation was carried out through Discursive Textual Analysis (DTA). The results attest to the validity of the thesis by showing that immersion in this authorial cycle provoked real fissures in the participants' technical consciousness. The confrontation with the realities of the "school floor" and with the subversions of Basic Education students shattered the myth of plug and play, forcing the pre-service teachers to face a zone of pedagogical risk. It is concluded that Teacher Authorship transcends software appropriation, configuring itself as a tensional process of alterity, empathy, and political literacy. The research also denounces applicationist curricular models and structural school precarization, arguing that, in the face of technology, a politically awakened teacher conscious of their intentionality is the most revolutionary “technology” in the classroom.
Teaching authorship of digital games and the shifts toward rupture with naive consciousness: the experience of pre-service Mathematics teachers through a sociotechnical lens
Keywords: Formação de Professores de Matemática; Educação Matemática; Autoria Docente; Jogos Digitais; Abordagem Sociotécnica; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade